LITERATURE REVIEW: ANALISIS PENGARUH LIFE STYLE (PEROKOK DAN NON PEROKOK) TERHADAP POSITIFITAS HASIL PEMERIKSAAN MIKROSKOPIS BAKTERI TAHAN ASAM (BTA) - Fetiara Dewi; Wahid Syamsul Hadi; Sri Martuti; Dhiah Novalina; Tri Dyah Astuti (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2021)
Tuberculosis (TB) is a disease with potentially infectious cough symptoms caused by the bacterium Mycobacterium tuberculosis. Half of the deaths caused by TB occur in men due to smoking habits and 3.2 times smokers can be at risk of developing pulmonary tuberculosis. Early diagnosis of tuberculosis cases can be done through microscopic analysis of sputum with Ziehl-Neelsen staining in order to prevent tuberculosis cases from increasing and reducing mortality due to tuberculosis. The objectives of this study are to determine the level of positivity of the results of microscopic examination of acid-fast bacteria (AFB) in smokers and non-smokers, to determine the effect of cigarettes on the results of microscopic examination of acid-fast bacteria (AFB), and to determine the risk factors that influence the positivity of the results of acid-fast bacteria (AFB) in smokers and non-smokers. This study employed literature review method with the PICO method on two databases, namely PubMed and Google Scholar. The level of positivity of AFB microscopic examination results in smokers found AFB results +3, +1, and +2 while in non-smokers found AFB results +1 and +3. The risk factors affecting the level of AFB positivity in smokers and non-smokers included more found in male than female, productive age, and smoking history. In smokers, the level of positive of the microscopic inspection of AFB revealed the most AFB +3 result, whereas non-smokers revealed the most AFB +1 results. Male, productive age (15-64 years), and smoking history are all risk factors for AFB positive in smokers and non-smokers (type of bidi cigarettes, consumption of 10-20 cigarettes per day, and the presence of exposure to cigarette smoke).